Jihad Between Islamic Jurisprudence and Practice of the Islamic State in Iraq and Syria - Khdir, Rebaz R. (European Scientific Journal, ESJ, 2018)
Islam is the extension of the monotheistic religions. It essentially claims for peace and tranquility but also allows war in some circumstances. War in Islam is referred to as jihad. However, jihad is border and includes spiritual struggle as well. Classical Islamic scholars interpreted combative jihad as self-defence against aggression and global war to spread Islam. The majority of modern scholars consider the political and cultural differences between the early periods of Islam and modern era. They interpret the concept as only self-defence and ask Muslims to resort to civil means to convey their message. However, some scholars and groups still follow the classical interpretation of the concept. Scholars generally set forth some preconditions for combative jihad. The preconditions are the existence of a reason, a purpose, permission of a legitimate ruler and adherence to humanitarian rules. ISIS launched intensive military attacks against the Islamic countries of Iraq and Syria between 2013 and 2014 and captured large areas after committing many atrocities and devastating the two countries. The group eventually announced an Islamic Caliphate and identified Abubakr al-Bagdadi as the Caliph. It later asked Muslims to pledge allegiance to its Caliph and join its ranks. This article argues that the ISIS war does not satisfy the Islamic jurisprudential conditions to be qualified as jihad because the group waged its war based on no religious reason for a political purpose without the authorization of a legitimate Islamic ruler and outside of the confines of the humanitarian rules.